Validity and informativity enhancement of ultrasonic testing of cast parts of railway rolling stock - A. N. Kireev; Y. K. Sklifus; M. A. Kireeva (Advanced Engineering Research)
Introduction. Due to the process reasons, the structure of cast parts of the railway rolling stock (RRS) often has embedded flaws that affect drastically their strength. The degree of impact depends on many factors including the shape and location of defects in the product. The shape of the defect has the greatest effect under alternating loads. This often refers to dynamically loaded parts of the RRS underframe. The defect oriented perpendicularly to the direction of tensile loads reduces the component life to the maximum. To identify embedded flaws, the parts are subjected to ultrasonic testing by the classical pulse-echo technique. However, such methods require increased validity and informativity. For example, they do not provide the determination of the type and orientation of the defect. Materials and Methods. Features, advantages and disadvantages of the classical pulse-echo technique of the ultrasonic non-destructive testing, which is based on the registration of the following echo signals, are considered:  sent; reflected from the opposite surface (bottom) of the object;  reflected from the defect (if any). The pulse arrival time is proportional to the thickness of the part. If there is a defect, this time is proportional to the distance from the pulse input surface to the defect. This method can determine the presence of a defect, but it cannot determine its type. Research Results. To determine the shape of a defect, a dualfrequency defectometry method is proposed. Its principle, algorithm and implemented analytical dependencies are described. When an echo signal from a defect is detected in the monitoring object, the amplitudes of the bottom signals and the amplitudes of the echo signals from the defect are measured at the ultrasonic wave frequencies of 2.5 MHz and 5.0 MHz. The defect shape factor is calculated from the analytical dependence; and the type of defect is determined. It can be volume (pores, shells, non-metallic inclusions) or planar (cracks, segregations, etc.). Discussion and Conclusions. A dual-frequency defectometry method to determine the type of defect under the manual ultrasonic testing of the RRS cast parts is proposed in the paper. For an express automated use of the proposed method, the software product NDTRT-07.04-L is developed, and its operation algorithm is described. The application of the technique can increase the validity and informativity of the test results